IMPLEMENTASI MODEL PEMBELAJARANCTL (CONTEXTUAL TEACHING AND LEARNING) DALAM PEMBELAJARAN PKn JENJANG PENDIDKAN DASAR - Mustika Syafi’aturrosyidah; Tri Rachma Zakiya Ningtyas; Zumaroh Zumaroh (PRODI PGSD UNIVERSITAS PGRI DELTA, 2022)
The problem experienced by elementary school children in learning Civics is the ability to understand concepts and interpret the learning they get by connecting the material taught by the teacher and related to students' experiences in real life. Therefore, it is necessary to apply Civics learning using the CTL (Contextual Teaching And Learning) learning model so that students are able to develop thinking skills to understand concepts and make sense of the learning they get by connecting the material taught by the teacher and associated with students' experiences in real life. In this regard, the research method used is data collection using literature studies with the results of learning effectiveness which depends a lot on the readiness and learning methods carried out by the students themselves, both independently and in groups.